EXPLORING THE FACTORS BEHIND THE LACK OF INTEREST IN TEACHING AMONG INDONESIAN EFL STUDENT TEACHERS: MOTIVATIONS AND IDENTITIES - Rahmi, Rahmi (Indonesian EFL Journal, 2024)
Teachers' motivations and identities have been popular topics of discussion among researchers. What has been missing in the discussion, though, is the investigation of the motivations and identities of student teachers who studied at an EFL teaching program but were unmotivated to be teachers. Therefore, this study investigated this missing topic in the Acehnese context in Indonesia. Five student teachers participated in this study. To collect the data, a reflective journal and a semi-structured interview were used. Codes were written, and themes about the student teachers’ motivations and identities emerged. This study showed three key findings. First, the student teachers uninterested in teaching were affected by extrinsic motivations to study in an EFL teaching program. Second, the student teachers progressively accepted their identities as EFL student teachers and shaped their desired and undesired future career identities. Third, fears and hopes fluctuated along with feelings of uncertainty about their future identities.